Optimización de la producción del campo dina terciarios a nivel de la formación honda mediante un trabajo de cañoneo, recañoneo y/o fracturamiento hidráulico (2022)
In this investigation, an optimization was carried out in the production of the Honda Formation in the Dina Terciarios Field through the implementation of three types of well intervention, executing a perforation, re-perforation and/or hydraulic fracturing work; Works that will allow the increase in hydrocarbon production of the Dina Tertiary Field. The study and analysis of the information was carried out to obtain the list of candidate wells, selected by evaluating the quality of the sands, resistivity, thickness, among other petrophysical properties used for the simulation of the nodal analysis; information validated by each of the three interventions that led to obtaining, through simulation in the specialized program, an increase in field production, within a financially profitable framework analyzed mainly with the financial cost-benefit indicator.